PERAN GURU DALAM MENGIDENTIFIKASI DAN MENANGANI PESERTA DIDIK TUNA CAKAP BELAJAR DI SEKOLAH DASAR UPTD SD NEGERI 3 LAWAHING - Marta Simey Famau; Novriani Mautang, Paulus Malaimabi, Petrus Mau Tellu Dony, Yessy Mata, Antonius A. Saetban (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this research is to examine gifted and disabled students (PWDs) who experience difficulties in understanding and processing academic information despite having average or above-average intellectual abilities. The presence of these students requires special attention and an appropriate approach from teachers. This study aims to describe the role of teachers in identifying and managing gifted and disabled students at the UPTD SD Negeri 3 Lawahing. The research method used is descriptive qualitative with observation, interviews, and documentation techniques. The research findings indicate that teachers play a crucial role in the early identification process through direct observation, informal assessment, and collaboration with parents and school stakeholders. In managing gifted and disabled students, teachers implement individual learning methods, utilize teaching aids, and strengthen student motivation. The conclusion of this study indicates that the active role of teachers significantly influences the success of inclusive education in elementary schools.